N-n-Butyl Haloperidol Iodide, a Derivative of the Anti-psychotic Haloperidol, Antagonizes Hypoxia/Reoxygenation Injury by Inhibiting an Egr-1/ROS Positive Feedback Loop in H9c2 Cells - Sun, Ting; Zhang, Yanmei; Zhong, Shuping; Gao, Fenfei; Chen, Yicun; Wang, Bin; Cai, Wenfeng; Zhang, Zhaojing; Li, Weiqiu; Lu, Shishi; Zheng, Fuchun; Shi, Ganggang (Frontiers in Pharmacology, 2018)
Early growth response-1 (Egr-1), a transcription factor which often underlies the molecular basis of myocardial ischemia/reperfusion (I/R) injury, and oxidative stress, is key to myocardial I/R injury. Silent information regulator of transcription 1(SIRT1) not only interacts with and is inhibited by Egr-1, but also downregulates ROS via the Forkhead box O1(FOXO1)/manganese superoxide dismutase (Mn-SOD) signaling pathway. N-n-butyl haloperidol iodide (F2), a new patented compound, protects the myocardium against myocardial I/R injury in various animal I/R models in vivo and various heart-derived cell hypoxia/reoxygenation (H/R) models in vitro. In addition, F2 can regulate the abnormal ROS/Egr-1 signaling pathway in cardiac microvascular endothelial cells (CMECs) and H9c2 cells after H/R. We studied whether there is an inverse Egr-1/ROS signaling pathway in H9c2 cells and whether the SIRT1/FOXO1/Mn-SOD signaling pathway mediates this. We verified a ROS/Egr-1 signaling loop in H9c2 cells during H/R and that F2 protects against myocardial H/R injury by affecting SIRT1-related signaling pathways. Knockdown of Egr-1, by siRNA interference, reduced ROS generation, and alleviated oxidative stress injury induced by H/R, as shown by upregulated mitochondrial membrane potential, increased glutathione peroxidase (GSH-px) and total SOD anti-oxidative enzyme activity, and downregulated MDA. Decreases in FOXO1 protein expression and Mn-SOD activity occurred after H/R, but could be blocked by Egr-1 siRNA. F2 treatment attenuated H/R-induced Egr-1 expression, ROS generation and other forms of oxidative stress injury such as MDA, and prevented H/R-induced decreases in FOXO1 and Mn-SOD activity. Nuclear co-localization between Egr-1 and SIRT1 was increased by H/R and decreased by either Egr-1 siRNA or F2. Therefore, our results suggest that Egr-1 inhibits the SIRT1/FOXO1/Mn-SOD antioxidant signaling pathway to increase ROS and perpetuate I/R injury. F2 inhibits induction of Egr-1 by H/R, thereby activating SIRT1/FOXO1/Mn-SOD antioxidant signaling and decreasing H/R-induced ROS, demonstrating an important mechanism by which F2 protects against myocardial H/R injury.